The Experimental Study of the Lens Wind Turbine Performance with Vortex Generator - Lohdy Diana; Joke Pratilastiarso; Arrad Ghani Safitra; Nu Rhahida Arini; Firman Yunan Saputra; Ar Rayyan Ikhsan Syahputra; Firdaus Fhudoli Putra (Invotek: Jurnal Inovasi Vokasional dan Teknologi)
Wind energy potential is available in several regions in Indonesia with wind ranges reaching 5 m/s. Wind turbine research continues to develop to produce optimal power. The aim of this research is to determine the performance of wind turbines equipped with diffusers or lens that put triangle fin vortex generator on lens’s surface. The turbine blade used Clark-Y that has a winglet angle of 45-degrees. There are three variations of lens wind turbine that were tested: without vortex generator, z/h=4.5, z/h=2.5, z/h=0.5. The research was carried out experimentally with fifth wind velocity 3 m/s, 3.5 m/s, 4 m/s, 4.5 m/s, and 5 m/s. The results analyzed to determine turbine performance are turbine rotation, the power produced due to wind direction. Based on the results of the experiments that have been carried out, the results were obtained a straight comparison between TSR and wind turbine rotation (rpm), and straight comparison between Cp and TRS. The Cp is largest in a lens wind turbine with a vortex generator z/h=0.5, which is 0.59 and has the highest power output of 473 watt.